PENGARUH KEPERCAYAAN PELANGGAN TERHADAP WORD OF MOUTH, NIAT BELI DAN RETENSI PELANGGAN GERAI INDOMARET DI SURABAYA - Muhamad Fahmi Rizanata (Journal of Business & Banking, 2014)
Trust on brand is strongly needed to sustain a business since trusted customers potentially leads to positive word-of-mouth (WOM), purchase intention, and customer retention. Further, WOM may also affect the purchase intention and, in turn, purchase intention may affect customer retention. This study tested the model exploring the existence of a modern retail in Indonesia that is Indomaret. Retail industry in Indonesia has been growing very well and Indomaret has also shown good stand although the coming competitors have also been stronger. This research distributed 125 Questionnaire to Indomaret customers and the data were processed using AMOS 20.00. The result shows that trust does not significantly affect purchase intention, but it significantly affects purchase intention through WOM and customer retention, without the mediation of purchase intention. The implication is that Indomaret has to be aware of building the quality of their value chain to improve customer trust and WOM.